The Effect of Eco-Efficiency and Quality Management System on Firm’s Performance: Moderating Role of Profitability and Leverage - Budiman Sutrisno; Wendy Wendy (Universitas Hayam Wuruk Perbanas, 2019)
This study examines the effect of an eco-efficiency and quality management system on firm performance moderated by earnings per share (EPS) and leverage. The results of panel data regression found that the eco-efficiency and quality management systems did not directly affect firm performance. The results of the interaction effect test indicated that profitability strengthened the effect of the quality management system on firm performance, yet weakened the effect of the eco-efficiency on firm performance. However, the leverage did not reveal any interaction effect. This research only examined the eco-efficiency by identifying whether the firms had a green-finance certification or not. It also strengthens the results of the previous studies by building an integrated model facilitating the effect of eco-efficiency and quality management systems on firm performance by involving two moderators that had not been found in the previous studies. This study implies –for the revolution of industry 4.0 issues— the stakeholders should be encouraged to strengthen the green economy as an essential business aspect in Indonesia. This study also recommends the importance of sustainable firm managerial studies on green-finance issues and environmental aspects.